Commentary (Research Highlights) - V. Choudary, Prabhakara (CNS & Neurological Disorders - Drug Targets, 2011)
Power Troubles in Parkinson's Disease Parkinson's disease (PD), which leads to motor and cognitive disabilities in 5 million people worldwide, is the second most common neurodegenerative disorder. Yet, a clear understanding of the mechanistic pathways and molecular machinery underlying the pathogenesis of this devastating disorder remains elusive, thus hampering the development of new therapeutic agents that are safer and more effective than levodopa (L-DOPA), a treatment introduced 40 years ago. The death of dopaminergic neurons in the substantia nigra and occurrence of α-synuclein-positive Lewy bodies in the brainstem and neocortex are neuropathological hallmarks of PD, explaining the classic motor symptoms of the disorder. Over the past decade, mutations in several genes have been shown to be associated with the early onset, Mendelian form of PD; similarly, polymorphisms in several loci have been established as risk factors for the common, non-Mendelian, late-onset sporadic PD. Together, these studies have clearly established the existence of a genetic component in the etiology of PD, which was long believed to be an environmental disease with no genetic component. Based on genetic data, dysfunctions in disparate cellular pathways have been postulated to play a causal role in PD pathogenesis. Prominent among them is the ‘mitochondrial dysfunction,’ which was prompted by the discovery of MPTP in 1976, followed by observations of signs of mitochondrial dysfunction in brain autopsies of subjects with PD, and mitochondrial location of three PD susceptibility gene products - Parkin, PINK1 and DJ-1. Evidence has since been mounting, suggesting that mitochondrial abnormalities could form part of PD neuropathology and result in impaired cellular energy production, increased free radical levels, or both. Now, adding weight to this idea, Zheng et al. (2010) report decreased expression of mitochondrial genes controlling cellular bioenergetics in PD. The researchers took a meta-GSEA (Gene Set Enrichment Analysis) approach to integrate 17 independent studies (with 221 PD patients and 221 control subjects) and analyze 522 gene sets to identify PD-associated molecular pathways. The analysis, conducted in three separate stages of replication, showed significant association of 10 gene sets (pathways). All 10 of these gene sets, which had never been linked to PD, were under-expressed at every stage. These gene sets implicate impairment of mitochondrial electron transport, mitochondrial biogenesis, glucose utilization, and glucose sensing early on in PD pathogenesis. Further, by performing a systems biology analysis, the authors demonstrated down-regulation of bio-energetic genes, including nuclear-encoded genes of the electron transport chain, whose expression is controlled by the master regulator PGC-1α (proliferator-activated receptor γ coactivator-1α). The role of PGC-1α in PD pathogenesis was validated using cellular disease models, wherein activation of PGC-1α resulted in increased expression of nuclear-encoded subunits of the mitochondrial respiratory chain and protected dopaminergic cells from the experimentally induced neurotoxic effect of two known risk factors of PD, i.e., rotenone and mutant (A53T) α-synuclein. This study is an elegant example of performing combined analysis of multiple gene expression studies using meta-GSEA to directly identify cellular pathways, in addition to genes, that are dysregulated in PD. The results, by associating PD with bio-energetic pathways that have not previously been linked, put the mitochondrial hypothesis of PD on a firmer footing and identify a new candidate therapeutic target (PGC-1α) for early intervention.